Is the use of the Problem-Based Learning Model through Instagram effective? A Review - Widarti, Hayuni Retno; Baharsyah, Allykha; Rokhim, Deni Ainur; Syafruddin, Afis Baghiz (Eclética Química, 2023)
Chemistry is still considered a difficult subject for students due to a lack of motivation and understanding. Implementing a problem-based learning (PBL) model with the media of Instagram can help students expand their critical thinking and problem-solving skills. To this end, 20 empirical research articles from inside and outside Indonesia were examined using the bibliometric analysis method to find research gaps and novelties as a basis for future research. The review shows various difficulties faced by students in studying chemistry. Instagram-based chemistry learning can help the learning process to be fun, innovative, easy to understand and not boring. Applying the PBL model to learning can help students develop critical thinking and problem-solving skills. The results of this analysis offer perspectives and innovations for teachers to deal with the problems faced by students, presenting innovations in learning, such as the use of Instagram and PBL models.